Chronic renal failure in Nottingham and requirements for dialysis and transplantfacilities. Issue 5969 (31st May 1975) - Dombey, S L; Sagar, D; Knapp, M S
Abstract : A retrospective study of uraemic patients covering 12 months of 1970 and a prospective survey covering six months in 1973-4 is reported for a population of almost 3/4million. The number of patients requiring regular dialysis treatment or transplantation or both is considered to be 45 per million of population under 65, 39 per million under 60, and 29 per million under 50 years of age.